M MANAJEMEN DANA BANTUAN OPERASIONAL SEKOLAH DALAM PEMENUHAN STANDAR SARANA PRASARANA MI MIFTAHUSSALAM 1 WONOSALAM DEMAK - KHOIRUL ANWAR; Subaidi; Sukarman (Fakultas Agama Islam Universitas Billfath, 2025)
This research aims to describe how School Operational Assistance (BOS) funds are managed to meet the facilities and infrastructure standards at Madrasah Ibtidaiyah (MI) Miftahussalam 1 Wonosalam Demak in the 2024/2025 academic year. The study addresses three research questions: 1. How are BOS funds managed to fulfill the facilities and infrastructure standards at MI Miftahussalam 1 Wonosalam Demak, in the 2024/2025 academic year? 2. What supporting and inhibiting factors affect the fulfillment of these standards and what’s the solution? 3. What outcomes are achieved in meeting the facilities and infrastructure standards through BOS-fund management? A qualitative descriptive approach was employed, with MI Miftahussalam 1 Wonosalam, Demak, serving as the research site. Data were collected through interviews, observation, and documentation. The findings reveal that: 1. BOS fund management covering budget planning, bookkeeping, auditing and accountability successfully met the facilities and infrastructure standards for classrooms, sports areas, places of worship, and the library. 2. Supporting factors include the principal’s commitment, school-committee backing, teacher involvement, and assistance from nearby institutions, whereas inhibiting factors comprise limited BOS funding, restricted land availability, and inadequate continuity in maintaining existing facilities. And efforts to overcome the limitations of facilities and infrastructure in school are carried out by establishing good relations between the school and the committee and several agencies around the school in order to create a more conducive environment for the development of education in school. 3. Overall, BOS-fund management at MI Miftahussalam 1 Wonosalam, Demak, yielded positive results in fulfilling the facilities and infrastructure standards.